PROGRAM PENGABDIAN KEPADA MASYARAKAT (PKM) KAMPUNG IKLIM (PROKLIM) DI KAMPUNG PEKIJING KELURAHAN KALANG ANYAR KOTA SERANG-BANTEN - Surachman Surachman; Efi Tajuroh Afiah; Ibrohim Ibrohim; Nuniek Permata (Yayasan Education and Social Center, 2023)
This paper is intended to present a comparative analysis of the implementation of a community empowerment based Kampung Climate's Leading Program (ProKim) in Pekijing Village, Serang City The result of this research indicates that both in Pekijing Village have emphasized aspects of community empowerment in the implementation of ProKlim mainly in climate change adaptation and mitigation activities. Empowerment and participation of communities in Pekijing Village is considered improperly managed. However, in substance, ProKlim has been well implemented in each locus. Further in practice, ProKlim, with a persistent management, is perceived to be able to manage a microclimate which gives a wider impact on temperature deterioration in the capital city